2016
DOI: 10.1177/0310057x1604400216
|View full text |Cite
|
Sign up to set email alerts
|

Chewing Gum in the Preoperative Fasting Period: An Analysis of De-Identified Incidents Reported to Webairs

Abstract: The role of preoperative fasting is well established in current anaesthetic practice with different guidelines for clear fluids and food. However, chewing gum may not be categorised as either food or drink by some patients, and may not always be specified in instructions given to patients about preoperative fasting. The aim of this paper was to review anaesthesia incidents involving gum chewing reported to webAIRS to obtain information on the risks, if any, of gum chewing during the preoperative fasting period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Some anaesthetists may draw the conclusion that a patient who has been chewing gum is inadequately fasted for sedation or general anaesthesia, and subsequently delay or cancel that patient who is otherwise fully prepared for their procedure. 2,3 The rationale for conducting this study was to provide evidence to practising anaesthetists to improve their ability to make clinical decisions about patient safety when faced with this problem. Our study detected an overall low incidence (7.1%) of fasting patients having a residual gastric volume >50 ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some anaesthetists may draw the conclusion that a patient who has been chewing gum is inadequately fasted for sedation or general anaesthesia, and subsequently delay or cancel that patient who is otherwise fully prepared for their procedure. 2,3 The rationale for conducting this study was to provide evidence to practising anaesthetists to improve their ability to make clinical decisions about patient safety when faced with this problem. Our study detected an overall low incidence (7.1%) of fasting patients having a residual gastric volume >50 ml.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, it is not known if chewing gum while fasting prior to elective surgery poses an increased risk of pulmonary aspiration if anaesthesia proceeds. 3 To compound this problem, there is no standard approach to the use of chewing gum in the fasting guidelines published by anaesthesia professional associations, including the Australian and New Zealand College of Anaesthetists (ANZCA), 4 European Society of Anaesthesiology (ESA), 5 Association of Anaesthetists of Great Britain and Ireland (AAGBI) 6 and American Society of Anesthesiologists (ASA). 7 This creates a situation where anaesthetists must use their own experiential judgement when deciding if a patient who has been chewing gum is adequately fasted for anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…It may be important to ensure that patients spit out chewing gum before the administration of anaesthesia or sedation (LOE- Low). [ 141 ] Chewing gum in the postoperative period is not common practice in India. A Cochrane review and 1 other meta-analysis have found early return of bowel function with chewing gum in the postoperative period (LOE- Low).…”
Section: Adult Sectionmentioning
confidence: 99%
“…A recent paper demonstrated that over a 5.5‐year period, five cases were identified in which gum was not detected pre‐operatively and was later found in the patient's mouth intra‐operatively or postoperatively. The authors recommended that a specific question on checklists for chewing gum might therefore be required .…”
mentioning
confidence: 99%